1981
DOI: 10.1002/food.19810250804
|View full text |Cite
|
Sign up to set email alerts
|

Der Einfluß des Backens auf den verfügbaren Lysingehalt in einigen industriell hergestellten Backwaren

Abstract: Der EinfluS des Backens auf den verfiigbaren Lysingehalt in einigen industriell hergestellten BackwarenM. HORVATI~. B. V A I I~ und M. G R~N E R Es wird die Abnahme des verfiigbaren Lysingehaltes und der biologischen EiweiBwertigkeit von einigen Backwaren unter den Bedingungen des technologischen Prozesses der Herstellung untersucht. Wihrend des Backens nimmt der Gehalt des verfiigbaren Lysins bei allen untersuchten Erzeugnissen signifikant a b (bei 95ziger statistischer Sicherheit). Die relative Abnahme, bezo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Similar changes were observed in our earlier investigations, in which the available lysine damage during baking of various standard hard biscuits ranged from 16 to 45%. 4 The results are also in accordance with other related studies, which found that the total decrease in lysine in biscuits and similar items amounted to 65% (46% lysine was destroyed and 19% inactivated). 5,7 The most important reaction connected with the damage to lysine bioavailability during food processing is condensation of its e-amino group with reducing sugars, which is an early stage of the Maillard reaction.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Similar changes were observed in our earlier investigations, in which the available lysine damage during baking of various standard hard biscuits ranged from 16 to 45%. 4 The results are also in accordance with other related studies, which found that the total decrease in lysine in biscuits and similar items amounted to 65% (46% lysine was destroyed and 19% inactivated). 5,7 The most important reaction connected with the damage to lysine bioavailability during food processing is condensation of its e-amino group with reducing sugars, which is an early stage of the Maillard reaction.…”
Section: Resultssupporting
confidence: 82%
“…This agrees with observations in our earlier investigations on the production of standard hard biscuits. 4 Furthermore, no characteristic relationship was found between the initial available lysine content and its relative decrease during baking. Such results may indicate that, in biscuits processed under severe heating conditions, other complex reaction mechanisms, not only the early stage of the Maillard reaction, were also involved in the damage to available lysine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation